2018
DOI: 10.1080/02770903.2018.1474364
|View full text |Cite
|
Sign up to set email alerts
|

Association between pediatric asthma care quality and morbidity and English language proficiency in Ohio

Abstract: In this urban, pediatric population with reliable interpreter services, limited English proficiency was not associated with worse asthma care quality or morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…T A G G E D E N D ACADEMIC PEDIATRICS LANGUAGE BARRIERS AND MANAGEMENT OF BRONCHIOLITIS interpreters. 13 In our study, we still found differences among families who requested an interpreter. Although there has been a robust body of research that indicates that medical interpreters improve patient satisfaction and understanding, 14−17 exactly how the use of medical interpreters impacts the disparities in patient management in the emergency department is unknown.…”
Section: Article In Pressmentioning
confidence: 47%
See 1 more Smart Citation
“…T A G G E D E N D ACADEMIC PEDIATRICS LANGUAGE BARRIERS AND MANAGEMENT OF BRONCHIOLITIS interpreters. 13 In our study, we still found differences among families who requested an interpreter. Although there has been a robust body of research that indicates that medical interpreters improve patient satisfaction and understanding, 14−17 exactly how the use of medical interpreters impacts the disparities in patient management in the emergency department is unknown.…”
Section: Article In Pressmentioning
confidence: 47%
“…However, in a recent study involving pediatric patients with asthma, there was no difference in pulmonary function testing or rates of asthma exacerbation in patients with limited English proficiency compared to patients who only spoke English. 13 The investigators concluded that the lack of differences found in patients with limited English proficiency may be due to the widespread availability of aOR indicates adjusted odds ratio; CBC, complete blood count; CI, confidence interval; ICU, intensive care unit; CXR, chest x-ray; and ED, emergency department.…”
Section: Article In Pressmentioning
confidence: 99%
“…[25][26][27] Additionally, we will determine whether we can use ICEES to demonstrate a relationship between asthma and established socioeconomic risk factors such as race, ethnicity, poverty, household educational attainment, and English language proficiency. [28][29][30][31][32][33][34] We note that several healthcare organizations have launched large-scale open-data initiatives, including COHD 9 and MIMIC. 10 Our results complement and extend these other initiatives by providing capabilities beyond those available through COHD or MIMIC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that LEP is associated with poor asthma outcomes and higher healthcare resource utilization [12][13][14]. Multiple studies show that LEP is independently associated with lower use of preventive healthcare, poorer health behaviors linked to chronic disease, and a longer length of hospital stay for diabetes diagnoses [15][16][17].…”
Section: Rationale For the Current Studymentioning
confidence: 99%